Searching for patterns of innovative public service delivery : Institutional design in Finnish public sector context - Tuurnas, Sanna; Jäppinen, Tuula; Pekkola, Elias (Fagbokforlaget Vigmostad & Bjørke, 2021)
Red Comrades Save the Galaxy is one of the most popular adventure game series from the early period of game development in Russia in the late 1990s. It presents adventures of characters borrowed from the century-long tradition of the Russian anecdote, most fertile in Soviet times. The majority of late Soviet anecdotes reused tropes from popular films, such as Chapayev (1934), and TV series, such as Seventeen Moments of Spring (1973) or Sherlock Holmes and Dr. Watson (1979). Some of the first experiments with the ludic medium relied on the same folklore material, which led to the birth of the ‘Russian quest’ adventure game. The same anecdotes inspired the new post-Soviet Russian novel in the 1990s, such as Chapayev and Void ([1996] 2001) by Victor Pelevin. In this chapter, we will examine this particular sub-genre to find out what was specific about Soviet/post-Soviet humour, and how exactly it revealed itself in early Russian adventure games.
Keywords: collaborative innovation; co-creation; institutional design; systemic adaptability; Finnish public administration; fi=Julkisjohtaminen|en=Public Management|